International migration and development in the Americas (ECLAC. Population Division SantiagoCL, 2001)
Covers five broad topics viz. migratory trends and patterns in the Americas; relations between migration and development; governance of migration and multilateral diplomacy; economic and social importance of migration; and human rights of migrants.
Keywords: MIGRATION